Mevalonate kinase deficiency: a survey of 50 patients - Bader-Meunier, Brigitte; Florkin, Benoit; Sibilia, Jean; Acquaviva, Cécile; Hachulla, Eric; Grateau, Gilles; Richer, Olivier; Farber, Claire Michèle; Fischbach, Michel; Hentgen, Véronique; Jego, Patrick; Laroche, Cécile; et al. (Pediatrics (Evanston), 2011)
The goal of this study was to describe the spectrum of clinical signs of mevalonate kinase deficiency (MKD). This was a retrospective French and Belgian study of patients identified on the basis of MKD gene mutations. Fifty patients from 38 different families were identified, including 1 asymptomatic patient. Symptoms began during the first 6 months of life in 30 patients (60%) and before the age of 5 years in 46 patients (92%). Symptoms consisted of febrile diarrhea and/or rash in 23 of 35 patients (66%). Febrile attacks were mostly associated with lymphadenopathy (71%), diarrhea (69%), joint pain (67%), skin lesions (67%), abdominal pain (63%), and splenomegaly (63%). In addition to febrile attacks, 27 patients presented with inflammatory bowel disease, erosive polyarthritis, Sjögren syndrome, and other chronic neurologic, renal, pulmonary, endocrine, cutaneous, hematologic, or ocular symptoms. Recurrent and/or severe infections were observed in 13 patients, hypogammaglobulinemia in 3 patients, and renal angiomyolipoma in 3 patients. Twenty-nine genomic mutations were identified; the p.Val377Ile mutation was the most frequently found (29 of 38 families). Three patients died of causes related to MKD. The disease remained highly active in 17 of the 31 surviving symptomatic patients followed up for >5 years, whereas disease activity decreased over time in the other 14 patients. Interleukin 1 antagonists were the most effective biological agents tested, leading to complete or partial remission in 9 of 11 patients. MKD is not only an autoinflammatory syndrome but also a multisystemic inflammatory disorder, a possible immunodeficiency disorder, and a condition that predisposes patients to the development of renal angiomyolipoma.